Implementasi Program Electronic Traffic Law Enforcement (ETLE) di Kota Serang: Evaluasi Efektivitas Kebijakan - Jannah, Lailatul; Pratiwi, Cintabi Dwi; Arwati; Nazwa, Sabita (Universitas Terbuka, 2024)
Research objective: to make people obedient and obedient in traffic. Seeing that traffic styles on the road are becoming more complex daily, as well as rampant violations, drivers who obey only when there are traffic officers have influenced the presence of the Electronic Traffic Law Enforcement (ETLE) policy. Serang City, as the central government in Banten Province, became the first city/district to implement ETLE, specifically in Jalan Veteran Serang City, in April 2021. As the years go by, ETLE in the jurisdiction of the Banten Regional Police continues to increase. The addition of ETLE location points in Serang City is becoming increasingly massive, so implementing the ETLE policy faces many challenges. This research was designed using qualitative methods based on the Policy Implementation theory by Merilee S. Grindle. The ETLE policy is a step taken by the government to create traffic discipline and order to minimize violations that occur on the highway. The research results stated that the implementation of the ETLE policy in Serang City was considered successful as measured by the quality of the implementation process, which was in accordance with what was stipulated and the achievement of policy objectives by what was targeted. This research also shows that the implementation of ETLE has had a significant positive impact on society. The community has a habitual pattern of obeying traffic and transparent law enforcement.